Older adults’ preferences for formal social support of autonomy and dependence in pain: development and validation of a scale - Bernardes, S. F. (2017)
Chronic pain among older adults is common and often disabling. Pain-related formal social support (e.g., provided by staff at day-care centres, nursing homes), and the extent to which it promotes functional autonomy or dependence, plays a significant role in the promotion of older adults’ ability to engage in their daily activities. Assessing older adults’ preferences for pain-related social support for functional autonomy or dependence could contribute to increase formal social support responsiveness to individuals’ needs. Therefore, this study aimed at developing and validating the Preferences for Formal Social Support of Autonomy and Dependence in pain Inventory (PFSSADI). One hundred and sixty five older adults with chronic musculoskeletal pain (Mage=79.1, 67.3% women), attending day-care centers, completed the PFSSADI, the revised Formal Social Support for Autonomy and Dependence in Pain Inventory, and a measure of desire for (in)dependence; the PFSSADI was filled out again 6 weeks later. Confirmatory factor analyses showed a structure of two correlated factors (r= .56): (a) Preferences for Autonomy Support (?=.99); and (b) Preferences for Dependence Support (?=.98). The scale showed good test-retest reliability, sensitivity and discriminant and concurrent validity; the higher the preferences for dependence support the higher the desire for dependence (r=.33) and the lower the desire for independence (r=-.41). The PFSSADI is an innovative tool, which may contribute to explore the role of pain-related social support responsiveness on the promotion of older adults’ functional autonomy when in pain.